PENGARUH KOMPENSASI, KARAKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KINERJA GURU ( Studi Pada Sekolah Menengah Kejuruan Pangudi Luhur Tarcisius 1 Semarang ) - Yesicha Hedhi Ekklesia, 13.05.51.0217; Rijanti, Tristiana (Students' Journal of Economic and Management, 2017)
This study analyzes the effect of compensation, job characteristics, and motivation on teacher performance. The object of research in this writing is Vocational High School Pangudi Luhur Tarcisius 1 Semarang. The sampling technique in this research is using the census of 62 respondents as sample by using questionnaire (questionnaire) by way of spreading the list of questions to the respondent in order to get information. The purpose of the study was formulated to determine the effect of compensation, job characteristics, and motivation on teacher performance.The collected data were analyzed using factor analysis to test the validity of question items, cronbach alpha formula to test instrument reliability, regression to test the magnitude of partial influence of each independent variable tested by regression analysis. The results of his research are: (1) compensation has a negative effect on teacher performance. (2) job characteristics have a positive effect on teacher performance. (3) motivation has a positive effect on teacher performance. Key Words             : Work Compensation, Characteristics, Motivation and Performance